PENERAPAN APLIKASI SAKTI DALAM PENGELOLAAN DANA PENDIDIKAN DI MADRASAH ALIYAH NEGERI 2 SAMARINDA - Fitrih Aulia Salam; Putri Eka Handayani; Suratman Suratman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Educational financial management requires an effective, transparent, and accountable system to support the implementation of quality education. One of the government's efforts to improve the quality of financial management is through the implementation of the Institutional Level Financial Application System (SAKTI). This study aims to examine the implementation of the SAKTI application in managing educational funds at MAN 2 Samarinda and to identify the obstacles encountered during its implementation. This research employed a qualitative approach with data collected through interviews, observations, and documentation. The collected data were analyzed descriptively to provide a comprehensive understanding of the implementation of SAKTI in financial management at MAN 2 Samarinda. The findings indicate that the SAKTI application has been implemented in all stages of financial management, including budget planning, budget proposals, budget execution, and financial reporting through an integrated system. The implementation of SAKTI has facilitated data management, improved work efficiency, and enhanced transparency and accountability in financial management. In addition, the security features embedded in the system help protect financial data effectively. However, several challenges remain, particularly related to internet network connectivity and the need to improve human resource competencies in operating the application. Therefore, adequate infrastructure support and continuous capacity building for users are necessary to optimize the utilization of the SAKTI application. Keywords: SAKTI, Educational Finansial Management, Transparency and Accountability